2017
DOI: 10.5114/ceji.2017.72808
|View full text |Cite
|
Sign up to set email alerts
|

Can mean platelet volume and neutrophil-to-lymphocyte ratio be biomarkers of acute exacerbation of bronchiectasis in children?

Abstract: IntroductionBronchiectasis (BE) is a parenchymal lung disease evolving as a result of recurrent lung infections and chronic inflammation. Although it has been shown in adult studies that mean platelet volume (MPV) and neutrophil-to-lymphocyte ratio (NLR) can be used as biomarkers of airway inflammation, knowledge is limited in the paediatric age group. The aim of our study is to investigate the potential of MPV and NLR as biomarkers that may indicate acute exacerbations of non-cystic fibrosis BE in children.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…11,24 The studies showed that PLR was more valuable than NLR in chronic inflammation, and it has been emphasized that PLR is an important inflammation marker. 9,25 Furthermore, there are also studies suggesting that PLR is a predictive marker in nasal polyposis cases. 12 Considering that another topic in ACP etiology is chronic sinusitis and inflammation, there may be changes in the inflammatory blood parameters of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,24 The studies showed that PLR was more valuable than NLR in chronic inflammation, and it has been emphasized that PLR is an important inflammation marker. 9,25 Furthermore, there are also studies suggesting that PLR is a predictive marker in nasal polyposis cases. 12 Considering that another topic in ACP etiology is chronic sinusitis and inflammation, there may be changes in the inflammatory blood parameters of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, there are studies in the literature showing that hemogram parameters are associated with the severity of the disease and recurrence in chronic inflammatory diseases. 9,10 Especially, the parameters correlated with the severity of systemic inflammation, such as the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), have also been shown to increase in cases of nasal polyposis. 11 Moreover, there are also studies suggesting that these parameters may be considered as an indicator for recurrence in cases of nasal polyposis.…”
Section: Introductionmentioning
confidence: 99%
“…MPV is an easily available and economical test and associated with thrombocyte activation in inflammatory conditions, however, contradictory results for MPV have been reported [29][30][31]7 . In the present study there was no relationship between MPV and severity of snake envenomation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a new biomarker of inflammation and can be used as an indicator and prognostic marker of inflammation. The neutrophilto-lymphocyte ratio (NLR) is a useful marker that predicts disease progression and mortality in inflammatory disease [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…[7] The same was stated in Turkey in 2015 where the neutrophil lymphocyte ratio could be used as an inammatory biomarker in acute exacerbation of bronchiectasis in children due to the physiological response of leukocyte circulation in the human body due to increased neutrophils and decreased lymphocytes. [8] Increased neutrophils occur during systemic inammation caused by delayed apoptosis and stem cell stimulation by growth hormone and decreased lymphocytes due to redistribution of lymphocytes to the lymphatic system accompanied by accelerated apoptosis. [7,[9][10] Research that assesses NLR begins in adults but still few in children where several studies report that an increase in NLR is associated with poor prognosis and ideal cut-off still varies with grades 3 to 5.4.…”
Section: Introductionmentioning
confidence: 99%